Evolución urbana del sector costero sur de General Pueyrredón - Juarez, Viviana Isabel (2001)
The southern portion of the coastal zone of the General Pueyrredon County was revalued in the last 20 years due to the aesthethic quality and sanitary conditions of the beaches where resort facilities were growing up. As the Supreme Court of the Buenos Aires province established in 1964 that the property of some of these beaches belong to privates ownerships, the administrative and urbanistic conditions are unique in Argentina. To the north, there is an area forested by the government that today is turistically exploited by privates. By the mean of vertical aerial photographs from 1957, 1964, 1970, 1977 and 1988, the evolution of the degree of construction of each block (n= 1,012) was evaluated, constructing a data base about 4 categories: 0-20%, 20-50%, 50-70% and 70-100% of construction. Each block was digitized in order to visualize thematic maps of land occupation. To present, we recognized a significant increase in the construction rate between 1977 and 1988 at the northern portion (Alfar-Chapadmalal interval). The value of the private property decreases 50% from the coast to 400-500 m landwards. These GIS procedures are the only way to monitor a probable depreciation of the ownership due to a regional deterioration of the environmental resource (beach erosion or water pollution) or obstacles to the access to the public domain (beach accessiblity or changes in the touristic services).